The Use of Vasopressor and Tourniquet to Reduce Hemorrhage during Myomectomy for Uterine Fibroid Removal: A Systematic Review - Djusad, Suskhan; Bimo, Ario; Futihandayani, Annisa (Open Access Macedonian Journal of Medical Sciences, 2024)
AIM: This review aims to evaluate the efficacy of vasopressin and tourniquet to reduce blood loss during myomectomy for uterine fibroids removal. BACKGROUND: Uterine fibroids and uterine leiomyomata, the most common benign tumors in women, can be difficult for women trying to conceive. Surgical therapy, such as hysterectomy or myomectomy, is one of the main treatment options. Excessive blood loss may occur during the procedure. Clamps or tourniquets around the uterine vessels are commonly used as anti-bleeding precautions during myomectomy. Intra-myometrial injection of vasopressin at the base of the largest fibroids and during hysteroscopic myomectomy is effective in reducing blood loss during laparoscopic myomectomy. METHODS: A literature search and computer-aided comprehensive electronic bibliographic search was performed using PubMed, Science Direct, SCOPUS, and Wiley for studies published from January 1997 to November 2017. RESULTS: Ten studies met the eligibility criteria and were included in this review. Each study assessed and compared the effects of vasopressin to the control group that exerts a hormonal hemorrhagic effect during myomectomy procedures. About 50% of vasopressin hemostatic agents have better outcomes in reducing blood loss. However, the use of both vasopressin and tourniquet simultaneously failed to reduce blood loss. DISCUSSION: Intramyometrial vasopressin injection resulted in a higher efficacy to decrease blood loss during myomectomy. Despite deciding which methods provide the most effective way to decrease blood loss, the two techniques showed excellent outcomes for the quality of the myomectomy procedure itself. CONCLUSION : Hemostatic medications have shown to have positive effects on myomectomy patients. The predicted volume of blood loss significantly decreased by both the mechanical tourniquet approach and the injection of the hormone vasopressin.